Iron loading, alcohol and mortality: A prospective study. Issue 3 (June 2019) - Schutte, Rudolph; Huisman, Hugo; Mels, Catharina M.C.; Botha, Shani; Kruger, Ruan; Smith, Wayne; Kruger, Iolanthé M.; Hawkins, Michelle; Smith, Lee; Breet, Yolandi; Schutte, Aletta E.
Summary: Background & aims: The relationship between total body iron and cardiovascular disease remains controversial and information absent in black sub-Saharan Africans in whom alcohol consumption tends to be high. The level of total body iron is tightly regulated, however this regulation is compromised by high alcohol intake causing iron loading. The aim of this study is to investigate total body iron, as represented by serum ferritin, and its interaction with measures of alcohol intake in predicting all-cause and cardiovascular mortality. Methods: We followed health outcomes for a median of 9.22 years in 877 randomly selected HIV negative African women (mean age: 50.4 years). Results: One hundred and five deaths occurred of which 40 were cardiovascular related. Ferritin averaged 84.0 (5th to 95th percentile interval, 7.5–533.3) ng/ml and due to the augmenting effect of inflammation, lowered to 75.3 (6.9–523.2) ng/ml after excluding 271 participants with high-sensitivity C-reactive protein (CRP) levels (above 8 mg/l). CRP increased by quartiles of ferritin in the total group ( P trend = 0.002), but this relationship was absent after excluding the 271 participants with high CRP values ( P trend = 0.10). Ferritin, gamma-glutamyl transferase and carbohydrate deficient transferrin (all P < 0.0001) were higher in drinkers compared to non-drinkers, but CRP was similar (P = 0.77). In multivariable-adjusted analyses, ferritin predicted both all-cause (hazard ratio, 2.08; 95% confidence interval, 1.62–2.68; P < 0.0001) and cardiovascular (1.94; 1.29–2.92; P = 0.002) mortality. In participants with CRP levels below or equal to 8 mg/l, the significant relationship remained between ferritin and all-cause (2.51; 1.81–3.49; P < 0.0001) and cardiovascular mortality (2.34; 1.45–3.76; P = 0.0005). In fully adjusted models, interactions existed between ferritin and gamma-glutamyl transferase, self-reported alcohol use and carbohydrate deficient transferrin in predicting all-cause ( P ≤ 0.012) and cardiovascular mortality ( P ≤ 0.003). Conclusions: Iron loading in African women predicted all-cause and cardiovascular mortality and the intake of alcohol seems mechanistically implicated.